Perancangan Desain Karakter Webcomic Bambang Sumantri Gagrak Wayang Jekdong - Izayanah, Fatihah Nahya; Ayuswantana, Alfian Candra; Arifianto, Pungky Febi (Universitas Pahlawan Tuanku Tambusai, 2024)
The loss of character and identity of the Indonesian nation in the younger generation is one of the negative impacts of globalization. One effort to strengthen the character and patriotism of the younger generation can be done by introducing local culture through modern media. Jekdong puppet is one of the local cultures that is rarely known by the younger generation. In Jekdong puppet, there is a story of a puppet character who has an inspiring patriotic character, namely Bambang Sumantri. Modern media that can be used to present the story of Bambang Sumantri is webcomic because it has advantages in terms of visuals and is effective in conveying character values. Character design, as an important basic element in comics, is made by transforming the form of Jekdong puppets into a more modern form using the ATUMICS method. With this character design, it is hoped that it can provide insight into the visual characteristics of Jekdong puppets and strengthen the patriotism of the younger generation.